1988
DOI: 10.1002/bit.260310717
|View full text |Cite
|
Sign up to set email alerts
|

Improved performance in viscous mycelial fermentations by agitator retrofitting

Abstract: For viscous mycelial fermentations it was demonstrated at the pilot-plant scale that the replacement of standard radial flow Rushton turbines with larger diameter axial-flow Prochem hydrofoil impellers significantly improved oxygen transfer efficiency. It was also determined that the Streptomyces broth under evaluation is highly shear thinning. Separate experiments using a Norcardia broth with similar Theological properties demonstrated that the oxygen transfer coefficient, K(L)a, can be greatly increased by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(24 citation statements)
references
References 8 publications
0
24
0
Order By: Relevance
“…Prochem hydrofoil impellers, which produce axial flow, have been tested for use in high viscosity mycelial fermentations. Buckland et al (1988a) demonstrated, in viscous mycelial fermentations at the pilot scale, that the replacement of standard radial flow Rushton impellers with larger diameter axial flow Prochem impellers, significantly improved the oxygen transfer efficiency. This improvement was attributed to the increase in size of the well-mixed, low viscosity cavern in the impeller region.…”
Section: -23 Influence Of Agitator Designmentioning
confidence: 97%
See 3 more Smart Citations
“…Prochem hydrofoil impellers, which produce axial flow, have been tested for use in high viscosity mycelial fermentations. Buckland et al (1988a) demonstrated, in viscous mycelial fermentations at the pilot scale, that the replacement of standard radial flow Rushton impellers with larger diameter axial flow Prochem impellers, significantly improved the oxygen transfer efficiency. This improvement was attributed to the increase in size of the well-mixed, low viscosity cavern in the impeller region.…”
Section: -23 Influence Of Agitator Designmentioning
confidence: 97%
“…Bulk blending is considered to be poor, using such turbines due to their tendency to compartmentalize (Nienow and Ulbrecht, 1985) and can lead to broth inhomogeneities of either pH or oxygen. This may be expected to be amplified in viscous, non-Newtonian broths (Buckland et al, 1988a;Nienow et al, 1995;Amanullah et al, 1998b). Bryant (1977) and Bajpai and Reuss (1982) have suggested that the critical factor that determines the overall effectiveness of oxygen uptake by microorganisms is the frequency at which cells are circulated through the highly oxygenated impeller region.…”
Section: -23 Influence Of Agitator Designmentioning
confidence: 97%
See 2 more Smart Citations
“…Sometime later in the early 1990s, Enfors and co-workers came to similar conclusions for fedbatch fermentations with respect to the nutrient feed (see for example, ). At around this time, it was shown that replacing Rushton turbines by high solidity ratio hydrofoil impellers which enhanced bulk mixing (spatial homogeneity) improved fermentation performance (Buckland et al, 1988), Only fairly recently, however has it been established experimentally that spatial and temporal chemical gradients exist in large-scale fed batch bio-reactors where additions of a concentrated, often viscous, carbon source at a single point onto the top surface of the growth medium means that mixing times are high (>~50s even at the 20m 3 scale (Vrabel et al, 2000)). Studies using computational fluid dynamics (CFD) based on Large Eddy Simulation (LES) also showed that considerable glucose gradients could be expected even when a standard 500 g/L glucose solution was fed to the liquid surface in a 22 m 3 bioreactor fitted with four Rushton turbines (Enfors et al, 2001).…”
Section: B Operational Constraints At the Large-scalementioning
confidence: 99%